Chronic FK506 treatment reduces amyloid β and tau levels in the hippocampus and cortex of 3xTg‐AD mice. (20th December 2022) - Fracassi, Anna; Marcatti, Michela; Saieva, Salvatore; Taglialatela, Giulio
Abstract: Background: Alzheimer's disease (AD) is the most common form of neurodegenerative dementia. While major histopathological hallmarks of AD are amyloid‐β (Aβ) plaques and neurofibrillary tau tangles, soluble oligomeric forms of Aβ and tau (TauO) have been identified as the most neurotoxic species involved in synaptic degeneration. Previous studies associate alterations of the phosphatase calcineurin (CaN) to AβO‐driven toxicity. We previously have shown that CaN mediates both the neurotoxic and cognitive effects of AβO and elevated CaN levels have been also shown in AD patients, suggesting a central role of CaN in AD onset and/or clinical progression. Our previous studies in mouse models demonstrated that an acute treatment with the CaN inhibitor FK506/Tacrolimus in Tg2576 acutely injected intracerebroventricularly with AβO restores memory function in these cognitively impaired animals. Moreover, we reported absence of AD in aging human chronically treated with KF506 following solid organ transplant. To deeper investigate the involvement of CaN in AD onset and progression, we used a 3xTgAD mouse model presenting both Aβ and Tau aggregates. Method: 7 month‐old 3xTg‐AD mice were chronically treated for two weeks with intraperitoneal administration of either FK506 (1mg/kg) or PBS. Using immunofluorescence and western blot analyses we analyzed the levels of CaN, total Tau and Aβ in hippocampal (dentate gyrus‐DG, CA1 and CA3) and cortical areas (frontal and parietal‐occipital cortex) in our experimental groups. Result: We found significantly decreased levels of CaN in DG, CA1 and CA3 and cortical areas in FK506 treated 3xTg‐AD mice as compared to 3xTg‐AD mice injected with PBS. Furthermore, performing double staining for Aβ and total Tau, FK506 treated mice displayed significant lower levels of Aβ and Tau in all the considered areas as compared to PBS‐treated 3xTg‐AD mice. These data suggest that the treatment with FK506 might trigger some mechanisms involved in the elimination of Tau and Aβ, i.e . autophagy. Conclusion: Our data confirm the role of CaN as a key player in AD. The reduced key AD pathology following CaN inhibition with FK506 suggests the use of an FDA approved drug as a potential treatment with rapid clinical translation to slow the progression of the disease.